SOSIALISASI SIAGA TSUNAMI BERBASIS SYARIAT ISLAM KEPADA SANTRI MADRASAH TSANAWIYAH SWASTA NURUL HUDA ACEH BARAT - Fatimah Siti Zahara; Mohamad Gazali; Rina Syafitri; Deki Farman; Miftahul Jannah; Raboni Al fitrah; Syahrul Ramadhan; Rinawati Rinawati; Zuriat Zuriat (Universitas Teuku Umar, 2022)
Earthquake and tsunami disaster were caused the devastated the properties and victims. One of the area that vurnerable toward tsunami impact is West Aceh. One of the main factor that caused the many victims are decrease the knowledge of society regarding earthquake and tsunami disaster as well as the alert to face the disaster. Therefore, it is necessary to prepare the knowledge and skill regarding the alert of earthquake and tsunami disaster. It is become the author’s initiave for undertaking the socialization of tsunami alert based on sharia islam to Santri MTSS Nurul Huda West Aceh Regency. The empowering community method namely to give the understanding and skill with sharia islam approach to santri of MTSS Nurul Huda West Aceh. The result of empowering community program that already reached includes the coordination with partner, conducting of the planning before activity of empowering community, conducting the socialization of tsunami alert based on sharia islam. The successfully indicator of these activities through pre test and post test showed enhaching of understanding and skill of Partner in alert of tsunami disaster. Therefore, it is necessary to build the regeneration of santri as the agent of management disaster in Aceh area.